Fusarium Mycotoxins, Taxonomy and Pathogenicity - Stępień, Łukasz (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It has been over 200 years since Fusarium pathogens were described for the first time, and they are still in the spotlight of researchers worldwide, mostly due to the mycotoxigenic abilities and the subsequent introduction of harmful metabolites into the food chain. The accelerating climatic changes are resulting in pathogen population and chemotype shifts all around the world, thus increasing the demand for continuous studies of factors that affect the virulence, disease severity and mycotoxin accumulation in plant tissues. This Special Issue summarizes recent advances in the field of Fusarium genetics, biology and toxicology.